Charge-state distributions in collisions of H and He with magnesium. - Baragiola, R. A.; Salvatelli, E. R.; Alonso, E. V. (North holland publisher, 1973)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina